An analysis of the phenotypic features of chromosomes 22q11.1 deletion syndrome at Red Cross War Memorial Children's Hospital - Hendricks, Lesley Jill (Department of Paediatrics and Child Health, 2019)
Chromosome 22q11.2 deletion syndrome (22qDS) is an inherited autosomal dominant disorder. It is the second most commonly occurring syndrome, Trisomy 21 being the most common. It is the most common microdeletion syndrome. The clinical range of features with which affected individuals present is very broad and includes congenital heart disease (particularly conotruncal malformations), palatal abnormalities, characteristic facial features, and learning difficulties. In total, there are more than 180 different phenotypic features associated with 22qDS. Due to the wide variability of phenotypic features that can arise in 22qDS it is often difficult to know when to test for the syndrome. Oskarsdottir’s criteria are widely used in clinical recognition for 22qDS. However, in a study done previously at Red Cross War Memorial Children’s Hospital, this same criteria was found to only have a positive predictive value of 14% for 22qDS. This is likely due to the fact that Oskarsdottir’s study was based on a largely Caucasian study population. Our population in Southern Africa is largely non-Caucasian. Previous studies have confirmed that non-Caucasian population groups with 22qDS have different presenting phenotypic features. For this reason, in this study we sought to describe the typical phenotypic features with which children with 22qDS present in our local population in South Africa. A retrospective folder review was done of the phenotypic features of all patients who had had a FISH test done on the suspicion on 22qDS. A total of 144 patient folders were reviewed (72 patients who were FISH positive for 22qDS and 72 patients who were FISH negative and functioned as the control arm of this study). A review on the phenotypic features of children with 22qDS revealed the most common presentation to be congenital heart disease (44%), failure to thrive (33%), dysmorphic features (32%) and cardiac failure (25%). A positive family history was only noted in 13 patients. Of those patients with a positive family history of 22qDS, only 5% were proven FISH positive for 22qDS themselves (less than the 10% described in the literature). Younger children presented more frequently with CHD, while older children presented with developmental delay and dysmorphic features. In general, developmental delay, palatal abnormalities and feeding difficulties were less common in our study population than described in the literature. Our particular patient population presented with the following CHD: isolated VSD (46%), tetralogy of Fallot (20.8%), truncus arteriosus (14.5%), PS/pulmonary artery stenosis (20.8%) and interrupted aortic arch (6%). Interrupted aortic arch was found to be the most sensitive marker for 22qDS in children with cardiac lesions. The cardiac lesions with the highest positive predictive value for 22qDS was non-isolated VSD (54%). Dysmorphic features with the highest sensitivity for 22qDS included bulbous nose (75%), abnormal digits (64%) and posteriorly rotated ears (68%). Primary immune deficiency, thymus abnormalities, cleft palate and behavioural issues were described less in this study than previously described in the literature. In conclusion, it is clear that non-Caucasian populations have some unique phenotypic expressions of 22qDS. It is imperative that clinicians maintain a high index of suspicion for patients with 22qDS.